Protótipo de lente de contato terapêutica com membrana amniótica para utilização em Oftalmologia - Pinto Junior, Henrique Nunes [UNIFESP] (2019)
Purpose: The purpose of this project was to produce a prototype of biological contact lens, using amniotic membrane (AM), for therapeutic application in ophthalmology. Methods: Support rings were made for MA through the turning and 3D printing processes. Comparisons of production processes, materials, thicknesses, toxicity and grooves were evaluated. The PLA, Pet6, Flex3D BR, 43sPremium materials were tested in vitro, placed in contact with corneal and conjunctival epithelial cells in vitro and their toxicity assessed by the MTT viability test. Results: The rings that were turned and the 3D prototypes were well structured and viable for production process. The materials that were used did not present cytotoxicity to the corneal and conjunctival epithelial cells. Conclusion: The AM contact lens prototypes showed to be structured both through turning and 3D printing. Using PLA filament, it was found that the production of biological AM contact lenses for ophthalmology use is feasible.